Public policies in Amazon and its interface with the border towns of Tabatinga/Brazil and Letícia/Colombia - Colares, Marineth Lima (2016)
Integration and cooperation between countries is an effort of those involved to combat the basic problems of harmonious and sustainable manner, resulting in the development of countries. The present article has as objective to study the existence of public policies between the border towns of Tabatinga (Brazil) and Leticia (Colombia) for the development of these regions. It is based that the improvements of the basic conditions of life exceed the economic transformation, political and social situation of each region. For this, the analysis was dual, as it has examined the behavior of states and the level of interdependence between them. It has exploring the regulatory initiatives taken by the government of the involved exposing, or not, the development, the progress balanced and fair between them. Also, it explores the role of legal instruments that instruct the cooperation of international public policy. The process, therefore, required an analysis of the content present in the treaties, books and academic articles. From the researches in the samples mentioned above, there was recognized the need of diligence on the part of the two countries for the propagation of international cooperation. It is due in face of the lack of government action on the part of the leaders and of the international organizations of the two countries.JEL-Code | F59; O19; Q58.